MANAJEMEN KONFLIK DALAM PENDIDIKAN ISLAM - Zaitun Zaitun (An-Nida', 2011)
A organization both for in form of is formal, informal and non is formal, a leader needed to have an efficiency and skill in managing its subordinate especially in managing possibility emerge conflict. Conflict is a fair activity or process emerge in a complex organization. conflict is the condition of generated by existence of strength which each other interfering in. This strengths coming from human desire. Conflict is also interpreted with different idea, hostility and emulation. Different idea do not always mean difference of desire. Because of conflict coming from desire, hence different idea do not always mean conflict. Emulation very hand in glove its relation link with a few party side wish same thing but only one which possible getting it. Emulation unlike conflict but easy to inclined to conflict direction, especially if there are any emulation which oppose against order agreed on. Hostility is not conflict because conflict involver might possibly [do] not have to feel hostility. On the contrary one who each other inimical might possibly do not stay in situation of conflict. Conflict alone do not always have to avoid by because do not be negative always as a result. Conflict also earn happened [at] institute education of Islam, for that ynag can be [done/conducted] is how to manage, and look for solution of generated impact it. Conflict in organizational siuatu ought to to reach the target of healthy organization. Equally incidence of conflict in organization viewed as by an healthy organizational symptom. Thereby each ; every conflict that happened can overcome hotly cooperation to reach the target of with. With return which enough like, head earn quickly recognize, identifying and measuring the level of conflict and also as a result with positive attitude and its ability, a head will be able to control conflict to always there is, and ifwhen possible using it for the openness of organization.